HUBUNGAN PEMBERIAN ASI (AIR SUSU IBU) EKSKLUSIF DENGAN KEJADIAN DIARE PADA BALITA: LITERATURE REVIEW - Jamil, Atthahirah Muhammad (ProNers, 2021)
ABSTRACTBackground: The high incidence of diarrhea requires finding efforts to reduce its incidence. Efforts that can be done are exclusive breastfeeding. However, these efforts have not yet reached the maximum in their implementation. Objective: To identify and analyze the relationship between exclusive breastfeeding and the incidence of diarrhea in children under five. Methods: The research design used is the literature review method. Search literature using the SPIDER method in three databases google scholar, researchgate and EBSCO with journals published in 2015-2021. Results: From eight articles, it was found that there was a relationship between exclusive breastfeeding and the incidence of diarrhea in children under five. There is a relationship between breastfeeding and breastfeeding mothers' knowledge and information, mother's motivation and busy working mothers. Conclusion: There is a relationship related to breastfeeding for toddlers, namely knowledge and information known to breastfeeding mothers, mother's motivation, busyness at work.Keywords: exclusive breastfeeding, diarrhea, toddlers.ABSTRAKLatar Belakang: Kejadian diare yang masih tinggi mengharuskan untuk mencari upaya dalam menekan angka kejadiannya. Upaya yang dapat dilakukan yaitu pemberian ASI eksklusif. Namun, upaya tersebut masih belum mencapai capaian maksimal dalam pelaksanaannya. Tujuan: Mengidentifikasi dan menganalisis keterkaitan antara pemberian ASI eksklusif dengan kejadian diare pada balita. Metode: Desain penelitian yang digunakan adalah metode literature review. Penelusuran literatur menggunakan metode SPIDER ditiga database google scholar, researchgate dan EBSCO dengan jurnal yang dipublikasi tahun 2015-2021. Hasil: Dari delapan artikel didapatkan hubungan pemberian ASI eksklusif dengan kejadian diare pada balita. Adanya keterkaitan pemberian ASI dengan pengetahuan dan informasi ibu menyusui, motivasi ibu dan kesibukan ibu bekerja. Kesimpulan: Adanya hubungan yang berkaitan dengan pemberian ASI terhadap balita yaitu pengetahuan dan informasi yang diketahui ibu menyusui, motivasi ibu, kesibukan dalam bekerja.